Teaching Through Hope and Growth: A Critical Incident Study of Gen Z Novice EFL Teachers in Rural Kalimantan Barat - Keny, Anatasia; Kuswandono, Paulus (Jambura Journal of English Teaching and Literature, 2025)
The professional development of novice teachers has nowadays become an urgent concern, particularly in rural areas where contextual challenges are complex and multifaceted. While formal training continues to dominate professional development discourse, there is growing recognition that critical, emotionally charged experiences, often unplanned and situated within local realities, play a pivotal role in shaping teacher identity and growth. This research aims to investigate how critical professional experiences influence the development of five Gen Z novice English teachers in rural Kalimantan Barat, Indonesia. Beyond classroom-centered perspectives, this study examines incidents arising from interactions with school leaders, peers, parents, and the broader community. Guided by a qualitative interpretive paradigm, this research adopts the Critical Incident Technique (CIT) and uses thematic analysis, the research captures the data through semi-structured interviews and reflective narratives. Findings indicate that critical incidents not only challenge novice teachers emotionally and pedagogically but also serve as catalysts for reflection, adaptation, and resilience. The study highlights the value of context-specific, experiential learning in fostering professional growth. These results suggest the need for localized, reflective professional development and rural-responsive educational policies.